Characteristics of Public Open Space Area in the Kampung Settlement (Case Study: Kampung Cungkeng) - Asriana, Nova; Rahmah, Fanny Fatti; Mezzaluna, Nadia Almira (Journal of Architectural Design and Urbanism, 2024)
This study investigates the characteristics of public space areas in kampung settlement, Kampung Cungkeng, Teluk Betung, Bandar Lampung, Indonesia. The study aims to identify the public space utilization and the elements moulding open space in this urban kampung. This study is to identify the characteristics of public space, the social interaction of communities and the dynamic interplay between public space and activities. It identifies the utilization of public open space which communities or dwellers use to interact and socialize in some activities in Kampung Cungkeng. The research is framed by qualitative method descriptively through collecting data and observing areas is accomplished by a snapshot surveying in a certain time. The method of data analysis is constructed by technical quality analysis based on facts and perception. The findings are the shortage of public space availability influences dwellers’ interaction and they bond engagement in semi-public zones, such as terraces and yards, where dwellers share the private house area to facilitate social activities. The lack of public space availability makes folks reorganise the existing public space and complete the additional facilities, features, or infrastructure to facilitate better social interaction and enhance comfort in Kampung Cungkeng.